Screening of Lactobacillus plantarum subsp. plantarum with Potential Probiotic Activities for Inhibiting ETEC K88 in Weaned Piglets - Wang, Weiwei; Ma, Hao; Yu, Haojie; Qin, Guangyong; Tan, Zhongfang; Wang, Yanping; Pang, Huili (Molecules (Basel, Switzerland), 2020)
For screening excellent lactic acid bacteria (LAB) strains to inhibit enterotoxigenic Escherichia coli (ETEC) K88, inhibitory activities of more than 1100 LAB strains isolated from different materials, and kept in the lab, were evaluated in this study. Nine strains with inhibition zones, at least 22.00 mm (including that of a hole puncher, 10.00 mm), and good physiological and biochemical characteristics identified by 16S DNA gene sequencing and recA gene multiple detection, were assigned to Lactobacillus (L.) plantarum subsp. plantarum (5), L. fermentum (1), L. reuteri (1), Weissella cibaria (1) and Enterococcus faecalis (1), respectively. As investigated for their tolerance abilities and safety, only strain ZA3 possessed high hydrophobicity and auto-aggregation abilities, had high survival rate in low pH, bile salt environment, and gastrointestinal (GI) fluids, was sensitive to ampicillin, and resistant to norfloxacin and amikacin, without hemolytic activity, and did not carry antibiotic resistance genes, but exhibited broad spectrum activity against a wide range of microorganisms. Antibacterial substance may attribute to organic acids, especially lactic acid and acetic acid. The results indicated that the selected strain L. plantarum subsp. plantarum ZA3 could be considered a potential probiotic to inhibit ETEC K88 in weaned piglets for further research.